Multiple temporalities in indigenous justice and healing practices in Mozambique - Igreja, Victor (International journal of transitional justice, 2012)
Responses to Mozambique’s 1976-1992 civil war and its multiple legacies have taken place in different social and political contexts over time. This article analyses responses developed during wartime and in the postwar context in Gorongosa, a district in the centre of Mozambique. Mainstream transitional justice literature has tended to ground analysis in linear temporalities, assuming that peace agreements or military defeats are the starting point of transitions and that justice and healing interventions with predefined lifespans transform societies. This article argues that indigenous understandings and practices of justice and healing are constituted by multiple temporalities that blend present, past and future in contingent and contested ways and on an ongoing basis. Culturally effective responses to wartime violations both shift and take prewar, wartime and postwar temporalities into account. Analysis based on recognition of multiple temporalities allows for a comprehensive understanding of the continuities and changes in the meanings of justice and healing. This type of analysis also reveals that from a cultural perspective, transitional justice is better interpreted as an open-ended process in that nobody can predict the lifespan of indigenous processes that address violations committed during major armed conflicts.